Vienna blood. Season 3 [videorecording (DVD)] - Thompson, Steve (Stephen); Beard, Matthew, 1989-; Maurer, Jürgen (Actor); Finckh, Luise von, 1994-; McKenna, Charlene; Bullmore, Amelia, 1964-; Hill, Conleth, 1964-; Tallis, Frank (PBS, 2023)
1900s Vienna is a hotbed of philosophy, science and art, where a clash of cultures and ideas collide in the city's grand cafes and opera houses. Brilliant Dr. Max Liebermann is a student of Sigmund Freud, and together with Detective Inspector Oskar Rheinhardt, they investigate a series of unusual and disturbing murders.